Anti-DNA antibodies in discoid lupus erythematosus. Follow-up study. - Bresnihan, B (1977)
Anti-DNA antibodies have been detected previously in patients with chronic discoid lupus erythematosus (DLE) despite the absence of overt systemic manifestations. 27 patients with DLE were followed up 3 years after the detection of anti-DNA antibodies in 7. None had developed other features of systemic lupus erythematosus. We conclude that the occasional finding of anti-DNA antibodies in patients with DLE does not predict those likely to develop systemic disease.